Editorial - Vieira, Wilson; Cepêda, Vera Alves; Malta, Maria Mello de (Cadernos do Desenvolvimento, 2022)
Editorial. Cadernos do Desenvolvimento, Centro Celso Furtado, Rio de Janeiro, v. 16, n. 29, p. 7-8, maio-ago. 2021.